Performance evaluation and multi-objective optimization of a novel UAV propulsion system based on PEM fuel cell. (1st March 2022) - Bahari, Mehran; Rostami, Majid; Entezari, Ashkan; Ghahremani, Sheida; Etminan, Melika
Highlights: Integrating PEMFC in UAV propulsion system for increasing flight duration. Proposing a new propulsion system having high-thrust and fuel-efficient capabilities. Optimizing the propulsion system's weight and thrust for long-endurance flights. Abstract: The present study has developed and optimized a novel hybrid propulsion system for unmanned aerial vehicles (UAVs). This system has two independent power generation sources which are the proton exchange membrane fuel cell (PEMFC) and a single-stage turbocharged engine. Each of these two systems can be used independently or simultaneously to generate power and thrust. To study the performance of the proposed hybrid propulsion system, a comprehensive thermodynamic analysis has been performed. In order to find the best working condition for the system, the effect of various design parameters on system performance has been analyzed. Multi-objective optimization of the hybrid system using the NSGA-II algorithm has been carried out to maximize the generated thrust of the propulsion system while minimizing fuel consumption rate. These will be ideal conditions for long-endurance missions. The results revealed that fuel consumption rate and the generated thrust in optimized point are equal to 34.58 (mg/s) and 69.56 (N), respectively. Also, we achieved 62.41% thermal efficiency for the new proposed propulsion system. To study system reactions to deviation from design parameters, a sensitivity analysis has been performed which revealed that an increase in air compressor pressure ratio doesn't change the thrust but increases the flight duration by decreasing the fuel consumption rate. Also, increasing the number of cells increases the generated thrust and efficiency of the system, however, this will increase the fuel consumption rate which lowers the flight duration. So, it is a compromise between two contradicting features and design objectives to select the characteristics of the system. System performance in different altitudes has been also investigated. By increasing the altitude, the overall efficiency drops, and the fuel consumption rate will increase.